Fandoms, Trending Topics and Social Capital in Twitter - Recuero, Raquel; Amaral, Adriana; Monteiro, Camila (AoIR Selected Papers of Internet Research, 2012)
It is increasingly common to see hashtags about celebrities, musicians and famous people among the Trending Topics (TTs) on Twitter. In this paper, we examine fans strategies to put their hashtags in the Top Ten list of trending topics and the social values created and used during the process. To discuss these appropriations, we studied the case of hashtags created by fans from a Brazilian pop rock band, Restart. We used a quanti-qualitative approach through online and offline ethnography (with 71 interviews) and the collection and analysis of 20 Trending Topics and six networks extracted from them during the second semester of 2011. As results, we discuss how the groups of fans of Restart learned to create hashtags in a cooperative way in order to spread their relations with their idols; which strategies they used to create the hashtags and get them into the TTs; and how they fight back the tags created by anti-fans, generating what we call Fan Wars. Finally, we show how fans are able to create bonding ties, network clusterization and influence visibility of information in Twitter.